2019
DOI: 10.1016/j.jflm.2019.04.001
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of mental health services to a new strategic direction for sexual assault and abuse services

Abstract: A new strategy for sexual assault and abuse services was published by NHS England earlier this year. It called for better coordination of services along the Sexual Assault Referral Centre (SARC) pathway following a sexual assault including mental health services for children and young people and adults. Previous research has highlighted Highlights  There is new national strategy for sexual assault and abuse in England  The strategy promotes partnership  Mental Health (MH) Services are key partners for SARCs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Brooker, Edmondson 126 In this study of mental health services in the UK, only 16% reported having a formal referral pathway with a sexual assault service.…”
Section: Study Type 5: Mixed-methods Studymentioning
confidence: 83%
See 3 more Smart Citations
“…Brooker, Edmondson 126 In this study of mental health services in the UK, only 16% reported having a formal referral pathway with a sexual assault service.…”
Section: Study Type 5: Mixed-methods Studymentioning
confidence: 83%
“…Brooker, Edmondson 126 In a study of mental health services in the UK, only 7% reported having a strategy in place that addresses the needs of sexual assault survivors, and 32% reported training their staff in assessing trauma experienced by their clients, including sexual assault and sexual abuse.…”
Section: Study Type 5: Mixed-methods Studymentioning
confidence: 99%
See 2 more Smart Citations
“…There is a high prevalence of sexual assault experienced by people with mental health issues; however, very few mental health services have reported a pathway to SARCs following a disclosure of a sexual assault. 44 In addition, in WP5 we identified that, over a period of 10 years in one NHS mental health trust alone, 3000 women who had received some form of psychological therapy input (as indicated by CORE-10 outcome data) had a case note indication that they had experienced sexual assault. It is not known whether the psychological therapy was because of the impact of sexual assault or other reasons and, even if it was related to the sexual assault, whether it was the correct therapy (i.e.…”
Section: Pre-sexual Assault Referral Centre: Lack Of Prior Awareness ...mentioning
confidence: 99%